Molecular detection of the hpmA and ureA genes in clinical Proteus mirabilis isolates - Rosa Kareem Shameel; Marwa Hameed M. Alkhafaji (Ibn Al-Haitham Journal for Pure and Applied Sciences)
Proteus mirabilis is one of the most common Gram-negative bacteria that can cause UTIs. The purpose of this research was to identify virulence genes in P. mirabilis strains obtained from the urine of Iraqi patients diagnosed with urinary tract infections. From October 2022 to February 2023, AL-Imam Ali Hospital collected 100 urine specimens from patients exhibiting symptoms and signs of UTI. All specimens were identified based on morphological characteristics on media of culture like pale, non-lactose ferment colonies on MaCconkey agar, swarming on blood agar, and salmonella shigella agar for hydrogen sulfide production, more diagnosed via utilizing molecular detection and the VITEK system, giving positive results for twenty P. mirabilis isolates. The (ureA, hpmA) gene detection results revealed the presence of ureA in 18 cases(90%), and hpmA in 17 cases (85%). The molecular technique showed that the ureA and hpmA genes associated with virulence factor hemolysin (hpmA) and urease (ureA) genes are necessary for causing urinary tract infections